1990
DOI: 10.3181/00379727-193-43024
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Vesicular Stomatitis Virus Replication in Dexamethasone-Treated L929 Cells

Abstract: We previously demonstrated that dexamethasone treatment of L929 cells inhibited plaque formation by vesicular stomatitis virus (VSV), encephalomyocarditis virus, or vaccinia virus. We now have characterized the antiviral effects of glucocorticoids in L929 cells. Dexamethasone did not directly inactivate VSV nor did steroid treatment of L929 cells affect virion adsorption or penetration. The VSV yield in L929 cells treated with dexamethasone for a period of only 4 or 8 hr was decreased by 50% when cells were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Differences in timing and dose underlie many of the inconsistent and sometimes conflicting results across studies of GC therapy (Cain and Cidlowski, 2020). GCs are often used in combination with antiviral drugs to counteract painful inflammation and are known to inhibit the replication of some viruses (Lancz et al, 1990;Kim et al, 2017), However, this approach is controversial, because GC treatment has been suggested to increase the viral yield and susceptibility, thereby increasing lung lesions and increasing or prolonging shedding of viruses, such as SARS-CoV (Li et al, 2003), SIVs (Ali et al, 2013), HSV-1 (Erlandsson et al, 2002;Hara et al, 2009;Du et al, 2012;Pechan et al, 2014), MMTV (Parks et al, 1974;Indik et al, 2007), retroviruses (Solodushko et al, 2009), PRRSV-1 (Singleton et al, 2018) and FFV (Lee and Shin, 2018). Consequently, GC use is often hampered by the onset of adverse effects or resistance (Petta et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in timing and dose underlie many of the inconsistent and sometimes conflicting results across studies of GC therapy (Cain and Cidlowski, 2020). GCs are often used in combination with antiviral drugs to counteract painful inflammation and are known to inhibit the replication of some viruses (Lancz et al, 1990;Kim et al, 2017), However, this approach is controversial, because GC treatment has been suggested to increase the viral yield and susceptibility, thereby increasing lung lesions and increasing or prolonging shedding of viruses, such as SARS-CoV (Li et al, 2003), SIVs (Ali et al, 2013), HSV-1 (Erlandsson et al, 2002;Hara et al, 2009;Du et al, 2012;Pechan et al, 2014), MMTV (Parks et al, 1974;Indik et al, 2007), retroviruses (Solodushko et al, 2009), PRRSV-1 (Singleton et al, 2018) and FFV (Lee and Shin, 2018). Consequently, GC use is often hampered by the onset of adverse effects or resistance (Petta et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the assayed compounds exhibit better SI than 28-homocastasterone (20) which possesses the basic steroidal skeleton of all the synthetic compounds ( Table 3). Compounds 21, 28 and 29 were active against all the viruses assayed: HSV-1, HSV-2, measles virus (MV) and JUNV.…”
Section: Hormones: Brassinosteroids (Brs)mentioning
confidence: 98%
“…The inhibitory action of 6 against VSV was attributed to inhibition of viral protein synthesis and was not associated to interferon induction [20].…”
Section: Glucocorticoidsmentioning
confidence: 99%
See 1 more Smart Citation